A Simple and Approximately Optimal Mechanism for an Additive Buyer - Babaioff, Moshe; Immorlica, Nicole; Lucier, Brendan; Weinberg, S. Matthew (SIGecom Exchange, 2014)
In this letter we briefly survey our main result from [Babaioff el al. 2014]: a simple and approximately revenue-optimal mechanism for a monopolist who wants to sell a variety of items to a single buyer with an additive valuation.